The Canadian Eskimo co-operative movement - Godt, P. (Polar Record, 1964)
Prior to World War II, little contact was made with the Eskimo of northern Canada, other than by early explorers, missionaries, Hudson Bay traders and the Royal Canadian Mounted Police. With the war, a new importance was attached to the Canadian Arctic, and it became a strategic area. Men and equipment moved in, airstrips were constructed, large buildings were erected to house the men and machines, and almost overnight the twentieth century had arrived.